REACH Story of Change: Monitoring and modelling river water quality to protect Dhaka’s river system - REACH (University of Oxford, 2024)
The Ready Made Garment (RGM) industry in Bangladesh is one source of pollution into Dhaka’s heavily contaminated rivers. Industrial pollution together with domestic waste damages rivers, estuaries and coastal waters with serious impact on the health and livelihoods of people who live nearby. REACH has created river system models to evaluate domestic and industrial effluents in rivers, and contributed to the development of a new water quality monitoring network in Dhaka. The models have also been used to assess mitigation measures for river clean-up, both for a government-led USD 20 billion mitigation scheme in Dhaka, and for industry, to inform potential investment in water treatment measures. Since 2019, Primark, the Alliance for Water Stewardship (AWS) and the Partnership for Cleaner Textiles (PaCT) representing many of the major international RMG companies, have been collaborating with the REACH programme to understand and respond to pollution from their factories.